THE EFFECT OF RETURN ON ASSET, CURRENT RATIO, DEBT TO ASSET RATIO TO THE VALUE OF PROPERTY, REAL ESTATE AND BUILDING CONSTRUCTION SECTORS COMPANIES LISTED ON IDX BEFORE AND DURING THE COVID-19 PANDEMIC (JEM17: Jurnal Ekonomi Manajemen, 2022)
The objective of this study is to determine the effect of return on assets, current ratio, debt to asset ratio to the value of property, real estate and building construction sectors companies listed on the Indonesia Stock Exchange (IDX) during 2019-2020. The selection of these research samples was based on the purposive sampling method resulting 16 companies. The methods used in this study were a descriptive quantitative method and a verification method. The data analysis technique used was a Dual Linear Regression Test Model by using the SPSS software application. The results of the study show that in the period before and during Covid 19, the variable of return on assets had a significant effect to the value of the company, the variable of current ratio had a significant effect to the value of the company (PBV) and the debt to assets ratio had a significant effect on value of the company (PBV).